Analysis of Wheat Wax Regulation Mechanism by Liposome and Transcriptome - Wen, Hongwei; Wang, Ying; Wu, Bangbang; Feng, Yanru; Dang, Yifei; Yang, Bin; Ma, Xiaofei; Qiao, Ling (Frontiers in Genetics, 2021)
As a barrier for plants to contact with the outside world, epidermal wax plays an important role in resisting biotic and abiotic stresses. In this study, we analyzed the effect of wax content on leaf permeability by measuring the wax loss rate in the leaf. To further clarify the wax composition of the wheat epidermis and its molecular regulation mechanism, we applied untargeted lipidomic and transcriptome analysis on the leaf epidermis wax of Jimai 22 low-wax mutant (waxless) and multi-wax mutant (waxy). Our research showed that the mutant waxy has a slow loss rate, which can maintain higher leaf water content. 31 lipid subclasses and 1,367 lipid molecules were identified. By analyzing the wax differences of the two mutants, we found that the main lipid components of leaf epidermis wax in Jimai 22 were WE (C19-C50), DG (C27-C53), MG (C31-C35), and OAHFA (C31-C52). Carbon chain length analysis showed that, in wheat epidermis wax, WE was dominated by C44 molecules, DG was mainly concentrated in C47, C45, C37, and C31 molecules, C48 played a leading role in OAHFA, and C35 and C31 played a major role in MG. Among them, DG, MG, and OAHFA were detected in wheat leaf wax for the first time, and they were closely related to stress resistance. Compared with the waxy, 6,840 DEGs were detected in the mutant waxless, 3,181 DEGs were upregulated, and 3,659 DEGs were downregulated. The metabolic pattern of main waxy components in the wheat epidermis was constructed according to KEGG metabolic pathway and 46 related genes were screened, including KSC, TER, FAR, WSD1, CER1, MAH1, ALDH7A1, CYP704B1, ACOT1_2_4, CYP86, MGLL, GPAT, ALDH, DPP1, dgkA, plsC, and E2.3.1.158 related genes. The screened wax-related genes were confirmed to be highly reliable by qRT-PCR. In addition, we found TER gene TraesCS6B03G1132900LC in wheat mutant waxless leaves for the first time, which inhibited the synthesis of long-chain acyl-CoA (n+2) by downregulating its expression. These results provide valuable reference information for further study of wheat epidermis wax heredity and molecular regulation.